Influence of Electronic Word Of Mouth, Product Quality and Price Fairness on Purchase Decision Wardah Cosmetic Products - Qalsum, Adzima -; Hidayat, Yusmar Ardhi; Pratiwi, Mona Inayah (Admisi dan Bisnis, 2024)
This research focuses on exploring the important role of positive reviews in increasing consumer purchasing decisions, as well as how Wardah, as one of Indonesia's most prominent beauty brands, can utilize social media marketing to amplify those positive reviews. Positive reviews have proven to be a key factor in building consumer trust and influencing purchasing decisions in today's digital era. The present study employs quantitative research methodology, utilizing nonprobability sampling approaches in the form of incidental sampling. A questionnaire was utilized for data collection, with 384 Wardah clients receiving it. The findings demonstrated that Price Fairness, Product Quality, and Electronic Word of Mouth all positively impacted purchasing decisions, sometimes concurrently. The goal of the study is to determine how consumers' decisions to buy Wardah cosmetic items are influenced by electronic positive vibes, product quality, and pricing justice. The study integrates social media marketing theory to find out how consumer interactions and reviews on digital platforms can strengthen online product recommendations so that they are expected to increase purchasing decisions. This study suggests that companies strengthen and manage their image online to maximize social media marketing through relevant content both in terms of quality and price. To encourage consumers to decide to buy Wardah cosmetic products